2006
DOI: 10.1111/j.1365-2648.2006.03936.x
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of clinical supervision: influence on job satisfaction, burnout and quality of care

Abstract: Nursing staff, especially those who have over 10 years' work experience, work in general care, have a nursing diploma, are non-tenured, work part-time and work 24-hour rotating shifts can benefit from clinical supervision. However, resources need to be invested in supervisor education and nursing staff need to be encouraged to start working in both supervisor and supervisee roles because of the positive effects on job satisfaction and quality of care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
63
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(76 citation statements)
references
References 52 publications
10
63
0
3
Order By: Relevance
“…In addition, this study reveals that CS definitely influences the development of skills important for patient safety care (see Table 2). The links between CS and patient safety are discussed in the literature [38,44,45] and Dawson [38] suggested that the former has some positive impact on the latter. Sullivan et al [29] highlighted that nurses need to be prepared for their future professional practice with tools in the form of knowledge, skills and attitudes, enabling them to continuously improve the quality and safety of care.…”
Section: The Relationship Between Cs and Patient Safetymentioning
confidence: 99%
“…In addition, this study reveals that CS definitely influences the development of skills important for patient safety care (see Table 2). The links between CS and patient safety are discussed in the literature [38,44,45] and Dawson [38] suggested that the former has some positive impact on the latter. Sullivan et al [29] highlighted that nurses need to be prepared for their future professional practice with tools in the form of knowledge, skills and attitudes, enabling them to continuously improve the quality and safety of care.…”
Section: The Relationship Between Cs and Patient Safetymentioning
confidence: 99%
“…7,8 There has been relatively little work to develop a framework for conceptualizing effective supervisory strategies in residency training in general and internal medicine in particular. International work in the field of psychology indicates that a lack of training in how to supervise not only impacts the performance of clinical supervisors but also that of their trainees.…”
mentioning
confidence: 99%
“…For the most part, supervisees (n=62, 95.4%) received clinical supervision from someone other than their line manager. This is consistent with best practice principles that advise against having dual and hierarchical relationships in clinical supervision (Dawson et al, 2012;Hyrkas et al, 2006;. Avoidance of dual relationships in clinical supervision facilitates the development of a safe learning environment for the supervisee and prevents administrative and managerial functions dominating the process (Beddoe, 2010).…”
Section: Supervision Arrangementsmentioning
confidence: 59%
“…For example, some studies show positive links between clinical supervision and professional development (Butterworth, Bell, Jackson, & Pajnkihar, 2008;Martino, Ball, Nich, Frankforter, & Carroll, 2008;Roche, Todd, & O'Connor, 2007), as well as decreased intent to leave and decreased burnout of workers (Begat & Severinsson, 2006;Hyrkas, Appelqvist-Schmidlechner, & Haataja, 2006). However findings from clinical supervision studies have been mixed, with some reports that supervisees have perceived clinical supervision to be ineffective for their practice (e.g.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation